Improving the Water Quality of Lake Toba, Indonesia - World Bank Group (World Bank, Washington, DC, 2019)
Lake Toba is a unique natural asset of global significance located in the North Sumatra Province of Indonesia. The long-term economic and environmental value of Lake Toba’s water is central to achieving multi-sector objectives as well as sustaining the livelihoods and well-being of communities in the catchment. Addressing the deterioration of Lake Toba’s water quality requires consensus and enforcement of the carrying capacity for fish production and catchment management measures, including the control of emissions from livestock manure and wastewater. Enabling adaptive management of the lake is dependent on timely and accurate data on lake dynamics and creating a cooperative, interagency platform for water quality monitoring. This is especially important as Lake Toba is not a homogenous water body but consists of discrete compartments that are not uniformly affected by pollution. The success of any interventions relies on the establishment of functioning and financially viable institutional arrangements that can facilitate cross-sectoral collaboration and bridge national-regional-district divides. Furthermore, the recommendations and the roadmap for improving water quality are relevant and transferable to the management of lakes and reservoirs across Indonesia and throughout the region.